Internet of Things and Health: A literature review based on Mixed Method - Cano, Ana Maria Chaves; Castillo, Verenice Sánchez; Gamboa, Alfredo Javier Pérez; Castillo-Gonzalez, William; Vitón-Castillo, Adrián Alejandro; Gonzalez-Argote, Javier (EAI Endorsed Transactions on Internet of Things, 2024)
The integration of technological advances into health sciences has promoted their development, but also generated setbacks and difficulties for digital transformation. In different areas, technology has modified the processes of diagnosis, teaching and learning, treatment and monitoring, which is why the study of new technologies and the models that support their introduction is essential. Internet of Things is one of these models, which, in turn, includes different models, devices and applications. Due to its breadth of exploitation options and benefits, in the health area this concept has been adopted and particularized as the Internet of Medical Things. With the purpose of achieving an approximation to the main trends and characteristics, a literature review study was conducted, based on mixed methods. Two studies were carried out with a sequential strategy, the first being bibliometric and the second a scoping review. The main results allowed us to describe the main trends in terms of bibliometric indicators, a thematic analysis in terms of areas, populations, benefits and limitations. It is concluded that there is a need for new interdisciplinary studies and lines for future research are presented.